A TURNING POINT FOR BANKING: UNRAVELING THE CHANGING LANDSCAPE OF BANKING ACTIVITY IN EUROPE SINCE THE COVID-19 PANDEMIC - ANDREA BELLUCCI; GIANLUCA GUCCIARDI (Journal of Financial Management, Markets and Institutions)
This study investigates how the COVID-19 pandemic affected the European banking system, focusing on lending activities and risk-taking behavior. We use a difference-in-differences (DID) approach to compare the performance of banks highly impacted by the pandemic with those operating in less affected countries. Our results indicate a negative impact on lending activities, as banks reduced their exposure to both individuals and businesses. Nonetheless, the impact on bank risk-taking was heterogeneous, as certain banks increased their risk-taking by relaxing their lending standards to support their borrowers while others tightened lending criteria. The reduction in total lending for the banking system was primarily driven by less capitalized banks — with a sharp decline in corporate loans combined with stability in mortgages and consumer loans — and those with limited access to public guarantee schemes. Different characteristics, such as size, profitability, and listing status, led to varied lending behaviors during the COVID-19 pandemic, with smaller and more profitable banks exhibiting greater resilience.